SUSEPTIBILITAS MAGNETIK TANAH SEBAGAI INDIKATOR TANAH LONGSOR DI DAERAH MALAMPAH KABUPATEN PASAMAN - Fitriah, Rahmatul; Afdal, Afdal (Universitas Andalas, 2024)
Soil magnetic susceptibility values have been measured in the Malampah area of Pasaman Regency using the rock magnetism method. Samples were taken from two areas where landslides had occurred and two areas where landslides had not occurred. Samples were taken at the top, middle, and bottom with 5 cm, 25 cm, and 50 cm depth variations. Measurement of soil magnetic susceptibility value was conducted using Bartington Susceptibility Meter MS2B. The results showed that the magnetic susceptibility value at low frequency (ꭓLF) at each sampling point is higher than the high-frequency magnetic susceptibility value (ꭓHF). Indicating that the research location contains superparamagnetic grains. From the range of ꭓLF values obtained, it is estimated that the magnetic minerals that control the samples are paramagnetic and ferromagnetic and the mineral type is estimated to be ilmenite (FeTiO3). Areas where landslides have occurred have a higher ꭓFD (%) value than areas where landslides have not occurred. The higher the ꭓFD (%) value, the more superparamagnetic grains will be in the sample. Superparamagnetic grains are smooth and easily absorb water. Adding soil mass due to water causes the soil to move quickly when on a slope.